Bacterial elimination via the photodynamic activity of a fullerene/light-harvesting antenna molecule assembled system integrated into liposome membranes. Issue 10 (16th September 2020) - Kawasaki, Riku; Antoku, Daiki; Ohdake, Reo; Sugikawa, Kouta; Ikeda, Atsushi
Abstract : Bacterial elimination was attained by singlet oxygen ( 1 O2 ) generated from fullerene derivatives via efficient energy transfer from photo-activated light-harvesting antenna molecules. Abstract : Ease of transmission and exceptionally high mortality rates make pathogen-based infections an ongoing global threat. Herein, a facile bacterial elimination process is described which is based on the photodynamic activity of fullerenes composed of light-harvesting antenna molecules integrated into liposome membranes. This was done to expand the absorption capabilities of fullerene derivatives. Efficient energy transfer from the photoactivated antenna molecules to the fullerenes enhanced antimicrobial activity without any harmful lytic activity against red blood cells even under irradiation.